Sowing the Seeds of Second Green Revolution - C.D. Mayee (Journal of Soil and Water Conservation, 2022)
When Dr. Suraj Bhan, President of the Soil Conservation Society of India (SCSI) requested me for delivering the Y.P. Bali Memorial lecture which is an annual feature of the Society to commemorate the memory of late Y.P.Bali. I was not sure whether I will be able to do justice to this feature. My predecessors of this event dealt useful scientific and development areas of Natural Resources to commemorate the memory and hence, I thought that I may not be able to do it because of my different scientific background. However, the opportunity of offering my personal tributes to late Bali was so tempting that I immediately consented for this lecture and decided to talk on the topic which would have been dear to him as he worked extensively in the development side of Ministry of Agriculture, Govt. of India.